BIOBEHAVIORAL THERAPY OF RHEUMATOID ARTHRITIS - N. A. Shabanova; O. S. Shubina; L. A. Ukolova; N. L. Tov (Бюллетень сибирской медицины, 2013)
The relevance of the study is connected with need to expand the arsenal of treatment methods patients with rheumatoid arthritis. The study examined the efficacy of biobehavioral therapy in a comprehensive program of treatment patients with rheumatoid arthritis (medical therapy in combination with biobehavioral therapy). It has been shown when compared with the control group (isolated drug therapy) maintaining  clinical  response  in  short-term  follow-up  study  in  the  intervention  group.  Statistically    significant relationship the volitional control of the alpha rhythm of EEG (increased power of the alpha rhythm) with a reduction in pain intensity in the in neurofeedback program and positive dynamics of the main characteristics of the alpha rhythm have been drmonstrated. Inclusion in the treatment program of arthritis biobehavioral approach has reduced the dose of pain medication, so reducing aggression of pharmacotherapy.